Analysis of mechanisms responsible for the formation of dark spots in organic light emitting diodes (OLEDs): a review - Mohammad, Muhammad Azrain; Mansor, Muhd Ridzuan; Sheikh Md Fadzullah, Siti Hajar; Omar, Ghazali; Dhar Malingam, Sivakumar; Nordin, Mohd Nur Azmi; Lim, L. M. (Elsevier B.V., 2018)
Organic Light Emitting Diode (OLED) is a new promising technology in lighting and display applications due to the advantages offered by the organic over inorganic materials. Nevertheless, the devices poor environmental stability and growth of dark spots has been a major concern for OLED devices. Based on the past literatures, several failure mechanisms have been proposed, suggesting that there is no particular model for the mechanisms of dark spots formation. In addition, the formation of dark spots is relatively obscure and unpredictable. On top of that, comprehensive reviews on the dark spots formation mechanism and the prevention methods are very limited at the current moment. Yet, both information are truly critical to be obtained and understood for OLED future development works. Thus, this paper reviewed particularly on the root cause formation of dark spots mechanisms in OLED devices. The dark spots are mainly formed due to the presence of foreign impurities and pinholes, as well as due to high current intensity. These root factor of elements will further enhance the degradation of OLED via bubble formations, electro-migrations, crystallizations and many other damaging processes. A few prevention steps have been discussed in order to reduce and prevent the dark spots from occurring such as the proper material selection and conducting the fabrication process in a controlled environment.